2005
DOI: 10.1523/jneurosci.4876-04.2005
|View full text |Cite
|
Sign up to set email alerts
|

Afferents and Homotypic Neighbors Regulate Horizontal Cell Morphology, Connectivity, and Retinal Coverage

Abstract: Horizontal cells are inhibitory interneurons with laterally oriented dendrites that overlap one another, contacting the pedicles of cone photoreceptors. Because of their regular spacing, the network of horizontal cells provides a uniform coverage of the retinal surface. The developmental processes establishing these network properties are undefined, but cell-intrinsic instructions and interactions with other cells have each been suggested to play a role. Here, we show that the intercellular spacing of horizont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
104
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 76 publications
(118 citation statements)
references
References 46 publications
14
104
0
Order By: Relevance
“…Thus, the differences seen here probably arise from differences in connectivity between photoreceptors and horizontal cells, rather than from differences in photoreceptor sensitivity. C57BL/6 horizontal cells have larger dendritic fields than those in 129/Sv retinas (Reese et al, 2005), suggesting that they may contact more cones; this could result in a larger suppression of rod inputs than in 129/Sv retinas.…”
Section: Methodological Considerationsmentioning
confidence: 98%
“…Thus, the differences seen here probably arise from differences in connectivity between photoreceptors and horizontal cells, rather than from differences in photoreceptor sensitivity. C57BL/6 horizontal cells have larger dendritic fields than those in 129/Sv retinas (Reese et al, 2005), suggesting that they may contact more cones; this could result in a larger suppression of rod inputs than in 129/Sv retinas.…”
Section: Methodological Considerationsmentioning
confidence: 98%
“…In these retinae, regular cellular spacing is disrupted when the interference occurs during a critical developmental window during which mosaic regularity is known to increase (Raven et al, 2005a). Furthermore, recent studies that have analyzed the HC mosaic in different strains of mice with a 2-fold difference in total HC number, or in mice with a genetically engineered reduction in normal HC number, have shown that the dendritic area of HCs varies inversely with HC density (Reese et al, 2005;Poché et al, 2008). From these data, it was concluded that mouse HCs employ homotypic cues to restrict dendritic growth, but how such dendritic interactions might mediate intercellular spacing remained unclear.…”
Section: Hcs Employ a Novel Methods Of Mosaic Formationmentioning
confidence: 99%
“…One other unresolved question stemmed from the fact that mature mouse HC dendritic arbors exhibit extensive overlap with neighboring cells (Fig. 4B-D) (Reese et al, 2005). Thus, it remained difficult to envisage how such homotypic signaling might be propagated through dendro-dendritic contacts, assuming that they interact with one another at the tips of their dendrites.…”
Section: Hcs Employ a Novel Methods Of Mosaic Formationmentioning
confidence: 99%
See 1 more Smart Citation
“…This large variation across mouse strains is present from the outset of retinal development (11) and is independent of variation in retinal area (9). Furthermore, these horizontal cells modulate their dendritic growth in relation to this variation in cellular density (12), indicating that the determinants of retinal nerve cell number also indirectly impact differentiation.…”
mentioning
confidence: 97%